Physical Fitness Level Of Elementary School Students In Physical Education, Sports, And Health Learning - Alif Aryadi Hardi; Muhammad Harliawan; Muhammad Fadli (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
Physical fitness is an important component of students’ physical and motor development and plays a significant role in supporting their participation and performance in physical education learning. However, information regarding the physical fitness level of elementary school students, particularly in the context of physical education learning at Lappae 64 Public Elementary School, remains limited. This study was conducted to fill this gap by providing an empirical description of students’ physical fitness levels and interpreting their implications for the implementation of physical education learning. This study employed a quantitative approach with a descriptive method. The population consisted of all students in grades IV, V, and VI at Lappae 64 Public Elementary School, totaling 40 students, comprising 22 male and 18 female students. Total sampling was employed; therefore, the entire population was included as the research sample. Students’ physical fitness was assessed using the Indonesian Physical Fitness Test (TKJI), which consisted of five components: the 40-meter sprint, bent-arm hang or pull-up, sit-up, vertical jump, and 600-meter run. Data were analyzed using descriptive statistical techniques by calculating the percentage distribution of students across physical fitness categories. The findings indicated that the largest proportion of students (45%) was categorized as having a moderate level of physical fitness, followed by the good category (22.5%), less category (20%), very good category (7.5%), and very less category (5%). These findings indicate that although most students demonstrated a moderate level of physical fitness, 25% of students were still classified in the less and very less categories. This distribution suggests that the existing physical education learning process has not yet resulted in an optimal level of physical fitness for all students and highlights the need for learning activities that systematically accommodate differences in students’ physical abilities. Therefore, physical education instruction should be strengthened through structured, progressive, and sustainable physical fitness activities integrated into regular learning. Scientifically, this study contributes empirical evidence concerning the physical fitness profile of elementary school students in the local school context, while practically, the findings can serve as a basis for physical education teachers and schools in developing more targeted fitness programs, monitoring students’ physical fitness periodically, and designing learning activities that support the improvement of students’ physical fitness.